The Effects of Primary Oxy-Salts on Anodizing Magnesium Alloy AZ91D - Yun, Yeoheung; Xue, Dingchuan; Halsall, Brian H.; Vanooij, William; Schulz, Mark J.; Shanov, Vesselin (Journal of Coating Science and Technology, 2014)
Anodization is known to be an effective way to slow down the initial corrosion rate of magnesium (Mg) and its alloys. Here, we investigated the specific use of oxy-salts to improve the corrosion resistance of anodizing coatings. Oxy-salts of silicate, phosphate, and carbonate were added separately to a sodium hydroxide alkaline electrolyte used to anodize Mg alloy AZ91D. The process was investigated in terms of anodizing behavior, the surface properties, and the corrosion behavior of AZ91D. Anodizing AZ91D using the silicate- containing electrolyte generated sparks, and produced a thicker and more corrosion-resistant layer than the other oxy-salts. In the process, MgO and SiO2 formed Mg2SiO4 at high temperatures. Coatings from the phosphate- and carbonate- containing electrolyte anodizations did not contain phosphorus or carbon. We also studied the effects of silicate concentration on the corrosion resistance and properties of the surface.